Black Cat. Vol. 19, As a sweeper - Yabuki, Kentaro (VIZ Media, 2009)
"After fighting their way to the center of Creed's Hideout, Train and Sven find their way blocked by the unexpected appearance of the Chrono Numbers. They're stopping the Sweepers so that they can take down Creed by themselves. But the Numbers find their own surprise--Creed appears to have become indestructible!"--P. [4] of cover.